Peningkatan Produktivitas Mesin Sanblasting Dengan Mengubah Setting Parameter Pada Mesin - Qomarotun Nurlaila; Muhammad Deni Wahyudin (SIGMA TEKNIKA, 2021)
The research was conducted to increase the productivity of the sandblasting machine on the SSIP model at PT. XYZ. The average productivity in March 2017 was 238 pieces / hour, which is below the productivity target set at 400 pieces / hour. Refer to root cause analysis low productivity on the sandblasting machine due to machine settings. The sandblasting machine settings before being changed were turn table parameters 15Hz , rotary gun parameters 50 Hz and pressure parameters 5 bar. By conducting several experiments on parameter combinations, parameter combinations can be obtained that can reduce cycle time and do not affect to product quality. The new sandblasting machine settings are 17 Hz turn table parameters, 60 Hz rotary gun parameters and 6 bar pressure parameters. The cycle time for setting up the new sandblasting machine is 9 seconds, equivalent to a productivity of 400 pieces / hour. So that productivity increases by 68% (from 238 pieces / hour to 400 pieces / hour).